Allocation of scarce resources during the COVID-19 pandemic: a Jewish ethical perspective. Issue 7 (10th April 2020) - Solnica, Amy; Barski, Leonid; Jotkowitz, Alan
Abstract : The novel COVID-19 pandemic has placed medical triage decision-making in the spotlight. As life-saving ventilators become scarce, clinicians are being forced to allocate scarce resources in even the wealthiest countries. The pervasiveness of air travel and high rate of transmission has caused this pandemic to spread swiftly throughout the world. Ethical triage decisions are commonly based on the utilitarian approach of maximising total benefits and life expectancy. We present triage guidelines from Italy, USA and the UK as well as the Jewish ethical prospective on medical triage. The Jewish tradition also recognises the utilitarian approach but there is disagreement between the rabbis whether human discretion has any role in the allocation of scarce resources and triage decision-making.